Eine weitere arabische Inschrift von der osttigrayischen Handelsroute: Hinweis auf eine muslimische Kultstätte in der "dunklen Periode"? - Smidt, Wolbert G.C. (Aethiopica, 2009)
This article discusses a fragmented Arabic inscription, which is kept in the rock-hewn church of Č̣ärqos Wǝq̠ro in eastern Tǝgray. The text could be read as one of the 99 names of God or an invocation of God. A stylistic comparison with Arabic inscriptions of eastern Tǝgray, Dahlak and other areas suggests that it was not produced locally, but rather imported, and dates to the 9th to 10th century approximately. It is thus one of the earliest witnesses for the presence of Muslims in Tǝgray in the “dark period” after the decline of Aksum. Style and content show that the inscription did not belong to a funeral complex, but rather to a place of worship. Its location points to a connection with nearby Nägaš, where Muslims revere the holy grave of the naǧāšī of the Ḥadīṯ, and which is located on the same route as Wǝq̠ro connecting the area with the Red Sea.